2022
DOI: 10.1039/d2sc01052f
|View full text |Cite
|
Sign up to set email alerts
|

Bisulfite-free and single-nucleotide resolution sequencing of DNA epigenetic modification of 5-hydroxymethylcytosine using engineered deaminase

Abstract: The discovery of 5-hydroxymethylcytosine (5hmC) in mammalian genomes is a landmark in epigenomics study. Similar to 5-methylcytosine (5mC), 5hmC is viewed a critical epigenetic modification. Deciphering the functions of 5hmC...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…The purified M.MpeI (or M.MpeI-N374K) was confirmed by SDS poly­(acrylamide) gel electrophoresis (PAGE, Supporting Figure S1). A3A protein was expressed and purified according to the previously described procedure, , and the details could be found in the Supporting Information.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified M.MpeI (or M.MpeI-N374K) was confirmed by SDS poly­(acrylamide) gel electrophoresis (PAGE, Supporting Figure S1). A3A protein was expressed and purified according to the previously described procedure, , and the details could be found in the Supporting Information.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Sequencing distinguishes C from 5mC as they are read as T and C, respectively. However, bisulfite treatment may lead to the degradation of up to 99.9% of input DNA due to the harsh reaction conditions. Liu et al developed TET-assisted pyridine borane sequencing (TAPS) for 5mC mapping . In TAPS, 5mC is oxidized to 5-carboxylcytosine (5caC) by TET protein and then reduced to dihydrouracil (DHU) by pyridine borane.…”
Section: Introductionmentioning
confidence: 99%
“…36 Recently, it was reported that APOBEC3A (A3A) protein exhibited high deamination activity towards both cytosine and 5mC in DNA. [37][38][39][40] The cytosine and 5mC could be readily deaminated regardless of sequence context. 41,42 Considering that 4mC contains a methyl group at the N 4 position and was partially resistant to bisulte-mediated chemical deamination, we reasoned that 4mC might also be resistant to deamination by A3A protein (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, such a DNA polymer is often hydrolyzed into volatile 2′-deoxynucleosides prior to ultra-high-performance liquid chromatography (UHPLC)–MS/MS detection. Benefitting from the enzymatic digestion of DNA into deoxynucleosides, the sensitivity of LC–MS/MS for detection of epigenetic DNA modifications improves over >1 million folds compared to that for the direct detection of the modifications in a short oligonucleotide. , Enzymatic digestion of DNA typically uses a combination of endonucleases (e.g., DNase I and benzonase) and exonucleases (e.g., nuclease P1 and phosphodiesterase I) to cut DNA, and an alkaline phosphatase [e.g., calf intestinal alkaline phosphatase (CIP)] to remove negatively charged phosphate groups in nuclease-cutting generated 2′-deoxynucleotides . These endo/exonucleases, for example, phosphodiesterase I and DNase II, are sensitive to inorganic salts and thus might fail to digest DNA completely.…”
Section: Introductionmentioning
confidence: 99%
“…14,23 Enzymatic digestion of DNA typically uses a combination of endonucleases (e.g., DNase I and benzonase) and exonucleases (e.g., nuclease P1 and phosphodiesterase I) to cut DNA, and an alkaline phosphatase [e.g., calf intestinal alkaline phosphatase (CIP)] to remove negatively charged phosphate groups in nuclease-cutting generated 2′-deoxynucleotides. 24 These endo/exonucleases, for example, phosphodiesterase I 25 and DNase II, 26 are sensitive to inorganic salts 20 and thus might fail to digest DNA completely. What is more, in the incomplete digestion, the release rate of distinct 2′-deoxynucleosides varies because of the substrate preference of DNase I.…”
Section: ■ Introductionmentioning
confidence: 99%